2010
DOI: 10.1097/aud.0b013e3181bb69db
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Population-Based Prevalence Rates of Unilateral Hearing Loss After the Application of Common Case Definitions

Abstract: This study demonstrates that different applications of well-accepted case definitions of UHL can influence population-based prevalence estimates, in this study by as much as a factor of 2. These findings highlight the importance of controlling for tympanometry status as a risk factor in such estimates. Which demographic characteristics and risk factors are significantly associated with hearing loss seem to vary depending on the case definition. These findings have implications for the interpretation of prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 11 publications
(21 reference statements)
1
55
0
2
Order By: Relevance
“…The age hearing loss was first suspected was around 4.3 years old, mostly the child's mother and the medical diagnosis was usually made at the age of 6 years, similar data to those reported in other studies 1,2,5,12 . Although has a neonatal hearing screening program in Brazil, late detection of hearing problems, usually during preschool age, is still common, especially in case children at risk to hearing loss 5,13 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The age hearing loss was first suspected was around 4.3 years old, mostly the child's mother and the medical diagnosis was usually made at the age of 6 years, similar data to those reported in other studies 1,2,5,12 . Although has a neonatal hearing screening program in Brazil, late detection of hearing problems, usually during preschool age, is still common, especially in case children at risk to hearing loss 5,13 .…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of unilateral hearing loss among schoolchildren varies from 3.0% to 6.3% depending on the case definition 1,2 . Many investigators have studied the etiology of unilateral hearing loss 3,4 and the most frequent causes of hearing loss are complications of viral infections and meningitis, especially in developing countries where these diseases are still very common.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 3 to 6% of schoolchildren have some degree of UHL (Ross, Visser, Holstrum, Qin, & Kenneson, 2010). However, the prevalence of UHL increases with age, and more than one out of ten children initially diagnosed with UHL will progress to bilateral hearing loss (Declau, Boudewyns, Van den Ende, Peeters, & van den Heyning, 2008; Haffey, Fowler, & Anne, 2013; Uwiera et al, 2009).…”
Section: Epidemiology and Detection Of Unilateral Hearing Loss In Chimentioning
confidence: 99%
“…The highest reported overall prevalence rate is 14% in a series of adolescents by Shargorodsky et al (2010), though this included 'slight' losses with thresholds of >15 dB HL. Ross et al (2010) demonstrated that prevalence figures depend on the definition of UHL, which varies among studies. Their study analysed data from a national populationbased, cross-sectional survey in the US (data from 1988 to 1994) to identify prevalence of UHL in children aged 6-19 years applying a range of commonly used audiological criteria (various combinations of thresholds and frequencies).…”
Section: Prevalence/aetiology Of Uhl In Childrenmentioning
confidence: 98%